Effectiveness of Beetroot Extract (Beta Vulgaris) on Cholesterol Levels and Kidney Histopathology in Aloxan-Induced Diabetic Rats - Jesika Jesika; Evelyn Angie; Gilbert Lister (Eduvest - Journal of Universal Studies, 2025)
Diabetes mellitus is a chronic metabolic disease that can cause severe complications, including lipid abnormalities and kidney damage. Beetroot (Beta vulgaris) contains bioactive compounds such as betacyanin and flavonoids with antioxidant and hypolipidemic properties, potentially improving lipid profiles and protecting renal tissues. To evaluate the effectiveness of beetroot extract (Beta vulgaris) on cholesterol levels and kidney histopathological features in alloxan-induced diabetic rats. This true experimental study used a pre-test and post-test only control group design involving 36 male white rats (Rattus norvegicus), divided into six groups: normal, negative control, positive control (metformin), and three treatment groups receiving beetroot extract at doses of 22.5 mg, 45 mg, and 90 mg/200 gBW. Diabetes was induced using alloxan monohydrate 150 mg/kgBW intraperitoneally. The extract was administered orally for 14 days. Cholesterol levels were analyzed using spectrophotometry, while kidney histopathology was examined using Hematoxylin-Eosin (HE) staining. ANOVA test showed significant differences in cholesterol levels among groups (p < 0.001). The treatment group receiving 45 mg/200 gBW demonstrated the most optimal cholesterol reduction compared to the negative control. Histopathological examination revealed improvement in glomerular and tubular structures in the treatment groups. Beetroot extract (Beta vulgaris) is effective in reducing cholesterol levels and improving kidney histopathology in alloxan-induced diabetic rats.